Kekerasan Simbolik dalam Wacana Keagamaan di Indonesia - Alfian, Andi (AL-ADYAN, 2023)
By borrowing Pierre Bourdieu’s theory, this study argues that religious discourse is one of the instruments often used by the dominant class (the majority, who are in power) to carry out symbolic violence against the dominated class (the minority, who are ruled). For example, through religious discourses that seem plural and open, the power and domination of the dominant class are continuously perpetuated. This study aims to analyze the symbolic violence that occurs in religious discourse in Indonesia, especially in the study of religion, by reviewing the discourse of “Agama vs. Kepercayaan” and “Moderasi Beragama.” According to Pierre Bourdieu’s theory, the symbolic violence referred to here is violence that does not appear as violence and is latent. Victims of this type of violence do not feel they are victims of violence as if what happened was natural and should have been. This study also argues that symbolic violence in religious discourse in Indonesia is widely produced in educational institutions, primarily through the hands of academics, because through educational institutions, discourses of “Agama vs. Kepercayaan” and “Moderasi Beragama” are formulated and then implemented in government policies, as if the discourse has accommodated all religions and beliefs, but only perpetuates the interests of the dominant class. In short, this study argues that religious discourses such as “Agama vs. Kepercayaan” and “Moderasi Beragama” are (re)produced for the interests claimed to be for the majority through educational institutions and so on and produce symbolic violence.